Nipple adenoma mimicking Paget’s disease: a case report - Younjung Cha; Eunhwa Park; Meesook Roh (Korean Journal of Clinical Oncology, 2026)
Nipple adenoma is a rare benign tumor arising from the lactiferous ducts of the nipple and may clinically mimic malignant breast conditions such as Paget’s disease. Accurate diagnosis is often challenging, and histopathological confirmation is essential. A 37-year-old woman presented with a 10-month history of a red tumor on the right nipple accompanied by erosion and bloody nipple discharge. Imaging studies revealed no definite causative lesion; however, a subtle hypoechoic lesion within the nipple was noted on ultrasonography. A punch biopsy demonstrated benign proliferative glandular structures. Surgical excision was performed with complete removal of the nipple and partial resection of the areola. Histopathological examination showed ductal proliferation with a dual epithelial and myoepithelial cell layer without cytologic atypia or invasive features. Immunohistochemical staining for p63 confirmed the presence of myoepithelial cells. The postoperative course was uneventful, and no recurrence was observed at the 6-month follow-up. Nipple adenoma should be considered in patients presenting with nipple lesions. Histopathological and immunohistochemical evaluation is essential for accurate diagnosis and appropriate management, allowing differentiation from malignant conditions and avoidance of overtreatment.